2015
DOI: 10.1016/j.econlet.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

The gender difference in the value of winning

Abstract: We design an all-pay auction experiment in which we reveal the gender of the opponent. Using this design, we find that women bid higher than men, but only when bidding against other women. These findings, interpreted through a theoretical model incorporating differences in risk attitude and the value of winning, suggest that women have a higher value of winning than men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 36 publications
(19 reference statements)
1
10
0
Order By: Relevance
“…In the same vein in the lab and in other domains, studies observe similar gender-pairing effects in ultimatum (Eckel & Grossman, 2001), dictator (Ben-Ner et al, 2004), multistage alternatingoffer bargaining (Dittrich et al, 2014), and in all-pay auction games (Chen et al, 2015). While there seems to be evidence on women's economic decision-making being affected by the gender of the party with whom they are interacting, explanations regarding women's preferences for same-gender competition are rather rare.…”
Section: Introductionmentioning
confidence: 76%
“…In the same vein in the lab and in other domains, studies observe similar gender-pairing effects in ultimatum (Eckel & Grossman, 2001), dictator (Ben-Ner et al, 2004), multistage alternatingoffer bargaining (Dittrich et al, 2014), and in all-pay auction games (Chen et al, 2015). While there seems to be evidence on women's economic decision-making being affected by the gender of the party with whom they are interacting, explanations regarding women's preferences for same-gender competition are rather rare.…”
Section: Introductionmentioning
confidence: 76%
“…Finally, there is strong evidence that female subjects bid more, resulting in lower profits, and weak evidence that they enter at a higher rate. Concerning bidding behavior, several authors have found gender differences in bidding behavior in environments without endogenous entry (Chen et al., , ; Schipper, ; Price and Sheremeta, ).…”
Section: Results From the Labmentioning
confidence: 99%
“…For example, when choosing to be rewarded by a tournament payment scheme or a piece-rate, women tend to choose the piece-rate over the tournament (Niederle and Vesterlund, 2007;Cason et al, 2010;Balafoutas and Sutter, 2012;Sutter and Glätzle-Rützler, 2015). However, in auctions and contests, women actually bid more than men (Ham and Kagel, 2006;Casari et al, 2007;Chen et al, 2013;Mago et al, 2013;Chen et al, 2015;Price and Sheremeta, 2015). Therefore, Figure 3 splits the average bid in the all-pay auction by school pair and gender.…”
Section: Gender Differencesmentioning
confidence: 99%
“…Obviously, the actual value of winning may not necessarily be reflected by the pure monetary value of the prize (Chen et al, 2015). Instead, it most likely incorporates different nonmonetary considerations, such as the non-monetary utility of winning (Sheremeta, 2010(Sheremeta, , 2013(Sheremeta, , 2015, status (Charness et al, 2013;Clingingsmith and Sheremeta, 2015), and recognition (Andreoni and Petrie, 2004;Samek and Sheremeta, 2014).…”
Section: Theoretical Predictionsmentioning
confidence: 99%